OPTIMALISASI MANAJEMEN PROGRAM EKSTRAKURIKULER ROHANI ISLAM - Jumriani Sandana; Hisban Thaha; Fauziah Zainuddin (Kelola: Journal of Islamic Education Management, 2021)
This research explores the issue of revitalizing the management of the Islamic spiritual extracurricular program which is the responsibility of the School Task Force Implementation Unit. The unit is expected to provide solutions to problems in public high schools including those faced by SMAN 11 Luwu. This research is very important in helping to improve the spiritual learning experience of students. This research design was descriptive qualitative. The approaches used in this research were a management and sociological approach. The management approach was the approach taken to find out how to revitalize the right Islamic Spiritual extracurricular management after being stopped for some time due to several problems. The sociological approach was an approach that sees how school principals, teachers and students respond to the revitalization of Islamic Spiritual extracurricular activities in schools. Management revitalization which is suggested from this research starting from preparing a curriculum for mentoring materials and program activities (Planning), managing management (Organizing), directing administrators to immediately carry out activities (Actuating), and still overseeing the course of program activities (Controling). In addition, it is necessary to determine that one coach still has a background in Islamic organizations. Preparation of student debriefing on the management of extracurricular spiritual organizations is carried out through training which is carried out after a new period of management is formed.